Accounting measurement and disclosure of intellectual capital in the financial statements of economic units - Saud Jaid Mashkwr; Jafar Faleh Nasser (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The research aims to measure intellectual capital in economic units through the use of some indirect calculation models in the measurement, which is the model of the present value of the future discounted revenue, and the model of the value added value of intellectual property. As well as the accounting disclosure of the value of intellectual capital in the balance sheet of economic units.Thereby increasing the credibility of the financial statements in the real expression of the financial position of economic units, and thus serve external users in the decision-making process. In order to achieve the objective of this research, the researchers used some accounting lists (balance sheet, salary list and wages) for a public company (Real Estate Bank) in Muthanna Governorate for the fiscal year (2012) to measure and disclose intellectual capital in their financial statements. The research concluded that there is a possibility for economic units to carry out accounting measurement of intellectual capital by following accounting models. In addition, there is the possibility of accounting disclosure of intellectual capital in the balance sheet of the economic unit. The research also showed that there is a clear difference, from the point of view of the users of the financial statements, on the status of the financial position of the economic unit after the disclosure process. The research recommended the need to increase the interest of economic unit in human capital in general and intellectual capital in particular, as this component is very important as one of the elements of production capacity contributing to the production process, in addition to adopting the necessary methods and standards that serve the measurement and disclosure of the capital Intellectuals in financial statements by international and domestic professional organizations.